2001
DOI: 10.1001/archpedi.155.7.771
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Outcomes of a Randomized Controlled Trial of a Community-Based Support Program for Families of Children With Chronic Illnesses

Abstract: A family support intervention can have beneficial effects on the mental health status of mothers of children with chronic illnesses. This type of intervention can be implemented in diverse pediatric settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 27 publications
2
96
0
2
Order By: Relevance
“…Social support is a concept that is perhaps less familiar to physicians. However, randomized trials of the provision of social support to new parents have shown lasting positive impacts for children, at least when done by nurses [49][50][51]. At this point, it seems reasonable to recommend an opportunistic approach of awareness, screening as much as possible, and intervening where leverage is available, based on physician, patient, and local resources.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is a concept that is perhaps less familiar to physicians. However, randomized trials of the provision of social support to new parents have shown lasting positive impacts for children, at least when done by nurses [49][50][51]. At this point, it seems reasonable to recommend an opportunistic approach of awareness, screening as much as possible, and intervening where leverage is available, based on physician, patient, and local resources.…”
Section: Discussionmentioning
confidence: 99%
“…There was no demonstrated effect on symptoms of depression. Health behaviours, health-care beliefs and knowledge and health-care use were not assessed in Ireys 2001 103 and no details of costs were given. Description of studies No screening interventions for men were identified.…”
Section: Discussionmentioning
confidence: 99%
“…103 The control group received a 'low dose' of the intervention, as they were given a telephone number through which they could reach an experienced parent, who had received no training and who did not initiate any telephone calls. Fewer than 3% of mothers in the control group called the number.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if network members are to provide support, they need to be kept apprised of the ego's needs (Azoulay et al, 2005;Cohen, 2004;O'Mara, 2005;Rabow, Hauser, & Adams, 2004). Although some small studies have been conducted which showed that appropriate social support for parents has benefits (Ireys, Chernoff, DeVet, & Kim, 2001;Norbeck & Tilden, 1983), very little research had been conducted into the social support needs of parents (and of patients in general), and their information-sharing choices in the context of a health crisis.…”
Section: Social Supportmentioning
confidence: 99%